IMPLEMENTASI PROGRAM POSYANDU LANSIA NURI VIII DI KELURAHAN TANJUNGBATU KOTA KECAMATAN KUNDUR - Lara Susanti; Bismar Arianto; Novi Winarti (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
The elderly posyandu program is the development of a government policy on elderly services and is implemented through the Puskesmas program by involving the elderly, families, regional apparatus and community organisations. Based on Government Regulation Number 43 of 2004 concerning the Implementation of Efforts to Improve the Social Welfare of the Elderly, the Government provides elderly services at various regional levels as a tangible form of elderly health services with the existence of elderly posyandu. The purpose of this study was to clearly determine the implementation of the Nuri VIII Elderly Posyandu program in Tanjungbatu Kota Village, Kundur Subdistrict In this study researchers used a qualitative approach method The informants of this study were the person in charge of the Elderly Program UPT Puskesmas Tanjungbatu, Nuri VIII Elderly Posyandu Cadres, and the elderly community. Data were collected through data collection techniques, namely observation, interviews, documentation and triangulation. The results of my research are the implementation of the Nuri VIII elderly posyandu programme in Tanjungbatu Kota Village, Kundur District has fulfilled these four indicators even though there are several problems with communication indicators and resource indicators, this is indicated by problems related to the lack of participation of the elderly community because those who actively follow are elderly people aged 55 years and over while the posyandu target is from the age of 45 years.